1990
DOI: 10.1016/0035-9203(90)90176-f
|View full text |Cite
|
Sign up to set email alerts
|

Results of echocardiographic examinations in a regional hospital of central Sudan

Abstract: Sixty-seven patients were examined with a small portable echocardiograph in Wad Medani Teaching Hospital in central Sudan. The cardiac alterations detected in the referred patients, namely valvular disease and pericardial effusion, suggested a high prevalence of inflammatory heart disease in this area. Other findings were dilatative cardiomyopathy, congenital heart disease, mitral valve prolapse and a cardiac mass. Echocardiographic examination of patients with advanced hepatosplenic schistosomiasis revealed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…However, since splenomegaly persists frequently also after cure, and since splenomegaly is not specific for malaria, the practical value of this finding is questionable. In certain cases, ultrasonography may contribute to differential diagnosis for those diseases involving the liver and/or the spleen which present characteristic ultrasonographic features: these include not only liver cirrhosis and malignancies but also infectious diseases occurring more frequently in endemic areas, such as echinococcosis, tuberculosis, bacterial endocarditis, chronic hepatosplenic schistosomiasis, amoebic liver abscess and acute fascioliasis (Richter et al 1990(Richter et al , 2003. Ultrasonography is indicated when splenic rupture is suspected (de Aguirre et al 1998;Yagmur et al 2000;Davies and Venkatesan 2002;Rapp et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…However, since splenomegaly persists frequently also after cure, and since splenomegaly is not specific for malaria, the practical value of this finding is questionable. In certain cases, ultrasonography may contribute to differential diagnosis for those diseases involving the liver and/or the spleen which present characteristic ultrasonographic features: these include not only liver cirrhosis and malignancies but also infectious diseases occurring more frequently in endemic areas, such as echinococcosis, tuberculosis, bacterial endocarditis, chronic hepatosplenic schistosomiasis, amoebic liver abscess and acute fascioliasis (Richter et al 1990(Richter et al , 2003. Ultrasonography is indicated when splenic rupture is suspected (de Aguirre et al 1998;Yagmur et al 2000;Davies and Venkatesan 2002;Rapp et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…A recent study demonstrated that PH patients with schistosomiasis may represent up to 30% of PH patients followed at reference centers in Brazil 25 . Furthermore, schistosomiasis is common in remote areas of less developed countries where health systems are not adequate and modern echocardiographic technologies are scarce 24,26 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding the diagnosis of early RV dysfunction in chronic SM, almost no information is available 5 . It is known that chronic cor pulmonale in hepatosplenic SM is uncommon 6,24,26,35 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations